From Sin to Treatment: A Very Brief Survey of the Relationship Between Political Power and End-of-life Decisions in Western Societies - Almeida, Ana Isabel (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2018)
Death and the circumstances under which one dies have been one of the most prolific themes in literature, the arts, and science in Western societies. Up until now, end-of-life practices in the West have relied more on curative treatments than on palliative care. The legalization of intentional practices such as euthanasia and assisted-suicide, in particular, is still a highly controversial topic. All this may lead us to think that the preservation of life and the intrinsic value of human beings inform current medical and political paradigms. In this article, I explore how Michel Foucault’s concepts of biopolitics and biopower have foregrounded the way political power has expanded its scope from the juridical right to “make live or let die” to the power of promoting life or rejecting it. To Foucault, death is the most secret part of our private life; it is where power meets its limit, thus the need to control every aspect of it, especially end-of-life decisions. I also illustrate my brief survey with three true life stories that may help us question the extent to which the contemporary organization of medical care may or may not be instrumental to political power in fostering the loss of autonomy of an individual facing death.